Measuring the Social Impact of Non-Formal Education Programs for Marginalized Students: An SROI Evaluation of the Education Centre Program in Jakarta - Sarah Nurhuda Nelson (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
This study evaluates the social impact of the Education Centre, a free non-formal tutoring initiative for lower-income urban children organized by the International Humanity Foundation (IHF) in Jakarta. Using a qualitative evaluative approach and the Social Return on Investment (SROI) framework, the study compares the social value generated by offline (face-to-face) and online learning methods implemented during the COVID-19 pandemic. Data were collected through semi-structured interviews, non-participant observation, and document analysis, involving 13 participants comprising students, parents, and volunteer teachers. The findings reveal significant differences in social impact: offline learning achieved an SROI ratio of 10.8:1, while online learning reached only 5.26:1. This discrepancy is attributed to stronger social interactions and the absence of digital barriers in offline learning, whereas online learning faced challenges related to limited device availability and internet connectivity. These findings underscore the crucial role of non-formal education in bridging educational gaps and highlight the need for hybrid strategies supported by digital inclusion policies. Academically, the study contributes by demonstrating the application of SROI in evaluating non-formal education programs within the urban Indonesian context.